Solvothermal Synthesis of Superhydrophobic ZnS Film - Wang, Xinmin; Yu, Chengqun; Wu, Junxi; Wei, Zhihua; Zhang, Yidong (Asian Journal of Chemistry, 2012)
In this work, a superhydrophobic ZnS film was successfully synthesized by a simple solvothermal route using Zn foil and sulphur powder as raw materials in an absolute ethanol solution at 160 ºC for 24 h. The products were characterized by X-ray diffraction, energy dispersive spectroscopy, scanning electron microscopy and contact angle. Results show that the obtained films were high crystallinity and uniformity. A possible reaction mechanism was proposed and discussed. It is found that the ZnS film exhibits superhydrophobicity due to its special nanoflakes structure. The average thickness of the ZnS nanoflakes film is ca. 120 nm.